Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
[tex]\begin{cases} 5x+2y=9 \\ x+y=-3\end{cases} \\ \\\begin{cases} 5x+2*(-3-x)=9 \\ y=-3 -x\end{cases} \\ \\\begin{cases} 5x-6-2x =9 \\ y=-3 -x\end{cases}\\ \\\begin{cases} 3x =9+6 \\ y=-3 -x\end{cases}[/tex]
[tex]\begin{cases} 3x =15 \ \ /:3 \\ y=-3 -x\end{cases} \\ \\\begin{cases} x =5 \\ y=-3 -5\end{cases} \\ \\\begin{cases} x =5 \\ y=-8\end{cases}[/tex]
[tex]\begin{cases} 3x =15 \ \ /:3 \\ y=-3 -x\end{cases} \\ \\\begin{cases} x =5 \\ y=-3 -5\end{cases} \\ \\\begin{cases} x =5 \\ y=-8\end{cases}[/tex]
5x+2y=9 x+y=3
change x+y=3 into x=3-y
plug that equation into 5x+2y=9 where x is.
5(3-y)+2y=9
then distribute.
15-5y+2y=9
15-7y=9
minus 15.
-7y=-6
divide both sides by -7.
y is equal to -6/7.
then go back to the first equation and plug in for y.
and then you will get x.
then you will have (y,x)
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.